Social and ethical aspects of media economics research - Gutierrez-Renteria, Maria Elena (Edward Elgar Publishing, 2019)
This work aims to contribute to research on media economics with a holistic vision, as suggested by Albarran (2017) and Godoy (2016), considering the importance of the ethical and social aspects in the media economy. The structure of the chapter is divided into four parts. Part one deals with the concept of the media firm according to the current digital environment of the industry. The second part deals with the role of ethics in media economy. The third part shows the media company links with the ethical aspects, while the final section includes the social aspects that have strong influence in the media economy in the 21st century. Finally, a research agenda is presented.
Keywords: ethics; media economy; digital environment; media company links